Application of 1-D analytical solution for salt intrusion investigation in the Belat Estuary - Chan, Tian Xian (2017)
In general, saline intrusion into the upper reach of river has caused problems especially for water intake activity. Recently, the water intake for human consumption in Kuantan has been reported to be salty. This means that the salt intrusion has reached the water intake station at Kampung Kobat, Kuantan river due to extreme low fresh water discharge as a result of El-Nino phenomenon. In this case, salt intrusion investigation is vital to determine the salinity level of the estuary so that the preventive measures can be taken if the observed salinity level in an estuary is near to the optimum level. In this research study, the salinity measurement in the Belat Estuary will be conducted. This is to make sure that residents around the Belat Estuary will have healthy water intake for consumption. The aims of this research are to: 1) investigate the salt intrusion in the Belat Estuary during spring tide; 2) apply the 1-D analytical solution for salt intrusion investigation in the Belat Estuary; 3) calibrate the shape factor for the Belat Estaury. The two parameters that need to be calibrated to fit the simulated salinity curve and the observed salinity data which are the Van der Burgh coefficient, K and tidal excursion, E. The data was collected on 28 Apr 2017. Result obtained from the geometry analysis shows that the shape of the Belat Estuary follows an exponential function. From the salinity analysis, the calibrated Van der Burgh‘s coefficient, K obtained is 0.65 and the value of tidal excursion, E is 6500m. The performance of the 1-D salt intrusion model was evaluated based on RMSE and NSE error analyses, and the results indicate that it is sufficiently accurate and reliable to be applied in the Belat Estuary.